EFFECTIVENESS OF ARTICAINE VS LIDOCAINE IN DENTAL PROCEDURES. - DR. N TAMILKKUMARAN,; DR. MADHULAXMI.M,; DR.P.U.ABDUL WAHAB, (International Journal of Pharma and Bio Sciences, 2014)
Local anesthesia causes a localized sensational loss due to the excitation depression or conduction process inhibition at peripheral nerve. Articaine and lidocaine belongs to amide group of local anesthesia. The aim of this paper is to evaluate the effectiveness of articaine and lidocaine in dental procedures.